Effect of Concentration of Liquid Vermicompost Fertilizer and ZPT Cytokinin on Growth and Yield oF Mustard Greens (Brassica Sinesis L): Pengaruh Konsentrasi Pupuk Organik Cair Kascing dan ZPT Sitokinin Pada Pertumbuhan Dan Hasil Tanaman Sawi Samhong (Brassica Sinesis L) - Rini, Risca Retno Setyo; Nurmalasari, Intan Rohma (Procedia of Engineering and Life Science, 2023)
This study aims to determine the concentration of liquid organic fertilizer vermicompost and ZPT cytokinins on the growth and yield of mustard greens (Brassica sinesis L). This research was conducted in Mojoruntut Village, Krembung District, Sidoarjo Regency from December 2022 to January 2023. This research method was carried out using a factorial randomized block design (RAK) consisting of 2 factors. The data obtained were processed using ANOVA, if there were differences between the treatments, the 5% BNJ test would be continued. The variables observed were plant height, number of leaves, fresh weight, dry weight, root length, and harvest index. Based on the results of the study it can be concluded that the application of liquid organic fertilizer from pineapple peel waste has a significant effect on the observation variables of plant height, number of leaves, fresh weight, dry weight and root length. While not significantly different in the harvest index observation variable. The optimal administration of liquid organic vermicompost fertilizer and cytokinin ZPT is with a concentration of 25 ml/l (P4) and 2ml/l (Z1).